Lessons learned from the birth and evolution of the EduFinland virtual community for educators - Kim Holmberg (Knowledge Management & E-Learning: An International Journal, 2012)
Educators around the world are experimenting with the possibilities virtual three dimensional worlds have for education and learning how to use these new environments efficiently. Virtual worlds have the potential to bring some new added value to education and educators can use them to create something that is not possible to do or show in traditional classrooms. Although a lot have been learned about virtual worlds and their potential, a lot more has to be learned before virtual worlds can become an integrated part of education on various levels. The article looks back at the birth and growth of the EduFinland community in the virtual world of Second Life and discusses lessons learned so far during the years of its existence.